Dengue Expanded Syndrome: An unusual presentation - Islam, Quazi Tarikul; Hossain, Homayra Tahseen; Khandaker, Md Abulkashem; Ahasan, HAM Nazmul; Majumder, Maksudul; Jabeen, Tajnuva (Bangladesh Journal of Medicine, 2018)
Dengue fever is a mosquito borne viral infection found in tropic & sub-tropic regions. The symptomatic dengue infection follows an uncomplicated course; however, unusual manifestations of this disease are now being increasingly reported as expanded dengue syndrome which incorporates wide spectrum of uncommon presentation of this common disease which does not fall into either dengue shock syndrome or dengue hemorrhagic fever. We report a case of a 30 year old lady who presented with high grade fever, rash, diffuse abdominal pain & vomiting, who ultimately developed shock and features of multi organ failure. We diagnosed her as a case of expanded dengue syndrome with multi organ failure ( hepatitis with very high transaminase levels, pancreatitis, acalculous cholecystitis, coagulation failure & acute kidney injury) with septicaemia. With prompt diagnosis and aggressive management, this potentially fatal patient was cured. Bangladesh J Medicine Jan 2018; 29(1) : 45-47